Fa'aliyyatut Ta'limiyyah 'Abru Al-Intirnit Bisti'mali Tathbiqi Al-Watsab Wa Al-Yutube 'Ala Ta'limi Qawa'idi Al-Lughatu Al-'Arabiyyati Laday Al-Thullab Kulliyyatu Al-Iqtishad Wa Al-A'mali Al-Islamiyyati Jaami'atu Tulung Agung Al-Islamiyyah Al-Hukumiyyah - Sirad, Mochamad Chobir (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Along with the development of information technology, Arabic language learning as part of the national education process is required to continue to update the methodology, improvement of teaching materials materials, improvement of educational facilities and infrastructure including learning media and improving the quality of human resources of teachers in order to be professional, innovative, and competitive or competitive.This research is motivated by the importance of learning Arabic rules to be studied even in the midst of this covid-19 condition. Arabic rules really need to be applied in learning Arabic because they determine the position / tarkib sentence and many levels difficulty. Since this covid-19 virus hit Indonesia, it is required to be social distancing and independent quarantine for all people in their respective places of residence at that time. This also has an impact on the process of teaching and learning activities in various institutions, both elementary, junior high, high school and university. All are lockdowns. One way to keep learning going is through online learning. Certainly has many advantages and disadvantages felt by everyone. Applications that are easy to use for this online learning process are WhatsApp and YouTube. Due to every smartphone today must have installed these two applications.